2009
DOI: 10.1111/igc.0b013e3181a5ff6a
|View full text |Cite
|
Sign up to set email alerts
|

The Level of RCAS1 Expression Is Inversely Correlated With the Number of Vimentin-Positive Stromal Cells in Epithelial Ovarian Cancer

Abstract: Expression of RCAS1 is significantly associated with clinical prognosis in 15 different types of human cancer. We have previously reported that RCAS1 expression is correlated with a decreasing number of vimentin-positive stromal cells in cervical cancer. Moreover, RCAS1 expression is related to the expression of matrix metalloprotease 1 and laminin 5 and angiogenesis. We examined whether RCAS1 contributes to connective tissue remodeling in epithelial ovarian cancer. RCAS1 expression was studied retrospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 16 publications
(22 reference statements)
1
21
0
1
Order By: Relevance
“…RCAS1 was secreted by ectodomain shedding through an activation of the MAPK pathway. Overexpression and ectodomain shedding of RCAS1 may contribute to tumor progression via not only stromal remodeling but also tumor cell proliferation [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…RCAS1 was secreted by ectodomain shedding through an activation of the MAPK pathway. Overexpression and ectodomain shedding of RCAS1 may contribute to tumor progression via not only stromal remodeling but also tumor cell proliferation [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…The infiltration of these cells corresponds to cancer progression (Dutsch-Wicherek et al 2009). RCAS1-positive macrophages were not detected in the ovarian cancer microenvironment, although RCAS1 was observed in both the cytoplasm and membrane of ovarian cancer cells within the cancer nest (Akahira et al 2004; Sonoda et al 2008; 2009). Moreover, RCAS1 expression in the cancer nest was higher in those patients who had advanced ovarian cancer (Akahira et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sonoda et al . found that the level of RCAS1 correlates inversely with the number of Vimentin positive cells within the microenvironment of the ovarian cancer (Sonoda et al 2009). These cells participate in connective tissue remodeling, which is in turn directly linked with overall survival rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, highly metastatic OSCC cells are likely to express RCAS1 as membranous or soluble proteins. In cervical and ovarian cancers, the number of cells that express mesenchymal marker vimentin is inversely related to RCAS1 expression, as remodeling of stromal tissue by vimentin results in tumor invasion and metastasis [35]. Moreover, enhanced RCAS1 expression in African Green Monkey kidney fibroblast cell lines COS-7 following introduction of the RCAS1 gene significantly promotes in vivo tumor growth via increase of vascular endothelial growth factor [36], which implies that RCAS1 affects tumor progression through lymph nodal metastasis.…”
Section: Discussionmentioning
confidence: 99%